The Portuguese Revolution (1640-1668). A European War of Freedom and Independence. - Rafael Valladares (2015)
Prudent readers know they should be wary of the first impression that may be created by a book’s title. First because the author of a work is not always responsible for choosing the title—the policy of publishing houses normally manages to impose itself—and second, and most importantly, because even when authors are free to choose their own title, there is always some doubt as to whether they have successfully managed, with just a few magic words, to convey the dense and complex message that a book contains.